A wet coating process for fluorine-containing rubber pressing pad and its application
Through the wet coating process, the charge adsorption effect is used to deposit inorganic matter, which solves the problem of poor use of glass fiber cloth in high temperature and high humidity environments, and realizes a high mechanical performance press pad, avoiding damage to the mechanical properties of glass fiber cloth.
Patent Information
- Application Number
- CN202410066327.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-17
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-01-17
AI Technical Summary
The existing fiberglass cloth is not effective in high temperature and high humidity environments, and common removal methods have a great impact on mechanical properties.
The wet coating process of fluoroelastic press pads is adopted, including glass fiber cloth pretreatment, sediment preparation, impregnation and drying, glue impregnation and molding, and the inorganic substances are deposited through charge adsorption effect to enhance the chemical reaction activity of the fiber surface.
The mechanical properties of the press pad are improved, making it excellent in use in high temperature and high humidity environments, and at the same time, the impact of paraffin is reduced and the mechanical properties of fiberglass cloth is avoided.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wet coating, in particular to a wet coating process of a fluorine-containing rubber pressing pad and application thereof. Background Art
[0002] At present, due to the characteristics of glass fiber such as low folding resistance and high brittleness, it is necessary to coat a mixture during its production to play the role of lubrication, bonding, and bundling during the production of raw silk. The lubricating components in the known glass fiber paraffin-type sizing formula are all oil substances such as paraffin, vaseline, engine oil or transformer oil. This glass fiber sizing has a high solid content, resulting in the sizing content of the drawn glass fiber yarn being more than 1%. The electronic cloth woven with this glass fiber yarn has a high sizing content, resulting in a high sizing residue on the cloth surface after simmering, which affects the use effect of the next process.
[0003] A common method for removing the impregnating agent on the surface of glass fiber cloth is the alkali removal method, which uses an alkaline solution to soak the glass fiber to remove the impregnating agent containing paraffin on the surface. Although this method can remove the impregnating agent efficiently at a low cost, it has a relatively high impact on the mechanical properties of the glass fiber cloth.
[0004] CN110937825B provides a wax-free sizing agent for high-silica glass fiber and a preparation method thereof, which can ensure that the high-silica glass fiber has excellent fiber bundling performance under high temperature and high humidity environment, does not affect the silica content and breaking tensile strength of the product during post-processing, reduces environmental pollution, and reduces production costs.
[0005] Patent CN105401423B discloses a post-treatment agent for electronic-grade glass fiber cloth, which is made of the following components: pH regulator, aminosilane coupling agent, fluorocarbon surfactant and deionized water. The electronic-grade glass fiber cloth treated with the treatment agent has the advantages of high mechanical strength, good heat resistance and high product yield.
[0006] However, from a cost perspective, a large number of glass fibers on the market still use sizing agents containing paraffin components in the preparation process. If the removal treatment is not performed, the use effect in a high temperature and high humidity environment will be greatly reduced. In view of the above phenomenon, the present invention provides a gentle and effective removal process and wet coating process, so that the prepared press pad has excellent mechanical properties. Summary of the invention
[0007] The object of the present invention is to provide a wet coating process for a fluorine-containing rubber press pad, and the coating process is as follows:
[0008] (1) Pretreatment of glass fiber cloth: immerse the glass fiber cloth in solution A for 30 min at a temperature of 35-45°C;
[0009] (2) Preparation of deposition solution;
[0010] (3) Impregnation and drying: impregnating the glass fiber cloth in the sedimentation liquid to obtain the modified glass fiber cloth A;
[0011] (4) Impregnation with glue: The glass fiber cloth A obtained in step (3) is immersed in glue for 30 minutes at a temperature of 35-45° C.; then taken out and dried naturally to obtain glass fiber cloth B;
[0012] (5) Molding: The glass fiber cloth B is heated, solidified, and molded.
[0013] As an embodiment of the present invention, the components of solution A include: 95wt% water, 0.5wt% starch, 1wt% potassium chloride, 0.5wt% phosphate, 2wt% alkaloids, 0.5wt% potassium hydroxide, and 0.5wt% minerals.
[0014] As an embodiment of the present invention, in step (2), the components of the deposition liquid include: ammonium chloride, water, ammonia water, and tetraethyl orthosilicate.
[0015] As an embodiment of the present invention, in the step (3), the immersion temperature is 60-70°C.
[0016] As an embodiment of the present invention, in step (4), the raw materials for preparing the glue solution include: polyol, isocyanate, chain extender, and catalyst.
[0017] As an embodiment of the present invention, the chain extender comprises a chain extender containing a tertiary amine group.
[0018] As an embodiment of the present invention, in the step (5), the heating temperature is 180-200°C.
[0019] A second aspect of the present invention provides a pressing pad prepared by the preparation process.
[0020] A third aspect of the present invention provides the pressing pad for application in the field of copper clad laminates.
[0021] By adopting the above technical solution, the present invention has the following beneficial effects:
[0022] The glass fiber cloth pretreatment method provided by the present invention can not only reduce the influence of paraffin wax, but also enable the glass fiber cloth to be used with excellent effect in a high temperature and high humidity environment; in addition, the present invention uses the charge adsorption effect to deposit inorganic matter on the surface of the glass fiber cloth, which can not only improve the mechanical properties of the pressing pad, but also help the glass fiber and the resin to be tightly together through physical interlocking; at the same time, the pretreatment method adopted by the present invention itself utilizes the charge effect, increases the chemical reaction activity of the fiber surface, and helps the chemical bonding reaction between the two. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The present invention provides a wet coating process for a fluorine-containing rubber pressing pad, and the coating process is as follows:
[0025] (1) Pretreatment of glass fiber cloth: immerse the glass fiber cloth in solution A for 30 min at a temperature of 35-45°C;
[0026] (2) Preparation of deposition solution;
[0027] (3) Impregnation and drying: impregnating the glass fiber cloth in the sedimentation liquid to obtain the modified glass fiber cloth A;
[0028] (4) Impregnation with glue: The glass fiber cloth A obtained in step (3) is immersed in glue for 30 minutes at a temperature of 35-45° C.; then taken out and dried naturally to obtain glass fiber cloth B;
[0029] (5) Molding: The glass fiber cloth B is heated, solidified, and molded.
[0030] Step (1)
[0031] The components of the solution A are: 95 wt% water, 0.5 wt% starch, 1 wt% potassium chloride, 0.5 wt% phosphate, 2 wt% alkaloid, 0.5 wt% potassium hydroxide, and 0.5 wt% minerals.
[0032] The minerals were purchased from Shandong Senhuatai Biotechnology Co., Ltd., and the nutritional enhancer mineral salt magnesium gluconate.
[0033] Steps (2) to (3)
[0034] The components of the deposition liquid include: ammonium chloride, water, ammonia water, and tetraethyl orthosilicate.
[0035] The specific steps of step (2) and step (3) are as follows:
[0036] S01 Dissolve 10.8g of ammonium chloride in 40.0g of ultrapure water, add 70.0mL of ammonia water, and dilute to 200mL with water;
[0037] S02: 10 ml of the above solution, the glass fiber cloth obtained in step (1), and 826.7 ml of ultrapure water are mixed together, and 693.2 g of tetraethyl orthosilicate is slowly added dropwise at a constant temperature of 80°C under ultrasonic stirring; after the addition is completed, the constant temperature ultrasonic stirring is continued for 12 hours; then the modified glass fiber cloth A is taken out and naturally dried.
[0038] Step (4)
[0039] The glass fiber cloth A obtained in step (3) is immersed in the glue solution for 30 minutes at a temperature of 35-45° C.; then taken out and dried naturally to obtain glass fiber cloth B;
[0040] Wherein, the preparation method of glue solution is as follows:
[0041] 32.50g polycarbonate diol (Mn=2000) and 10g fluorinated polyol (Mn=1000, purchased from Wuhan Kemik Biopharmaceutical Technology Co., Ltd.) were dehydrated at 110-120°C with a vacuum degree of 0.09MPa for 1h, and then added to a reaction flask equipped with a thermometer, a stirring rod, and a reflux condenser. 11.7g solid MDI and 0.10g dibutyltin dilaurate were added under nitrogen protection, and the mixture was reacted at 80°C for 2h. After cooling to 55°C, butanone (adjusting the solid content to 60%) was added, and 1.38g N-methyldiethanolamine and 1g 11-(triethoxysilyl)-1-undecylamine and 0.5g (triethoxysilyl) methanol; when the temperature drops below 45°C, add 2.00ml acetic acid, react for 30min, adjust the pH to 5-6 with 5% dilute hydrochloric acid, cool to room temperature, add a mixture of ethanol and water (volume ratio of 1:3), and adjust the solid content to 30%.
[0042] The glass fiber cloth A obtained in step (3) is immersed in the glue solution for 30 minutes at a temperature of 35-45°C; then taken out and dried naturally to obtain glass fiber cloth B.
[0043] Step (5)
[0044] The glass fiber cloth B was dried at 180 degrees Celsius for 30 minutes and solidified to obtain a pressed pad.
[0045] A second aspect of the present invention provides a pressing pad prepared by the preparation process.
[0046] A third aspect of the present invention provides the pressing pad for application in the field of copper clad laminates.
[0047] The inventors of the present invention found that the pressed pad prepared from the glass fiber cloth purchased from the market is easily damaged under high temperature or high humidity conditions; it was later discovered that the glass fiber would be coated with paraffin during the preparation process. Therefore, the glass fiber cloth needs to be pre-treated before use. The conventional treatment method is to use alkali treatment, but it will damage the surface of the glass fiber, thereby further affecting the mechanical properties. If a silane coupling agent is used for modification, it is found that due to the characteristics of paraffin, the effectiveness of the silane coupling agent is weak, and it will reduce the amount of resin infiltration later. Therefore, the inventors selected solution A for pre-treatment, reduced the influence of paraffin, and then used a quantum dot effect to perform inorganic deposition treatment on the glass fiber cloth, and then compounded it with the resin, thereby preparing a pressed pad with excellent performance.
[0048] The present invention is further explained below in conjunction with specific implementation modes.
[0049] Example 1
[0050] This embodiment provides a wet coating process for a fluorine-containing rubber press pad, and the coating process is as follows:
[0051] (1) Pretreatment of glass fiber cloth: immerse the glass fiber cloth in solution A for 30 min at a temperature of 40° C.; the components of solution A include: 95 wt % water, 0.5 wt % starch, 1 wt % potassium chloride, 0.5 wt % phosphate, 2 wt % alkaloid, 0.5 wt % potassium hydroxide, and 0.5 wt % minerals.
[0052] The minerals were purchased from Shandong Senhuatai Biotechnology Co., Ltd., and the nutritional enhancer mineral salt magnesium gluconate.
[0053] (2) Preparation of deposition solution;
[0054] (3) Impregnation and drying: The glass fiber cloth is immersed in the sedimentation liquid to obtain the modified glass fiber cloth A.
[0055] The specific steps of step (2) and step (3) are as follows:
[0056] S01 Dissolve 10.8g of ammonium chloride in 40.0g of ultrapure water, add 70.0mL of ammonia water, and dilute to 200mL with water;
[0057] S02: 10 ml of the above solution, the glass fiber cloth obtained in step (1), and 826.7 ml of ultrapure water are mixed together, and 693.2 g of tetraethyl orthosilicate is slowly added dropwise at a constant temperature of 80°C under ultrasonic stirring; after the addition is completed, the constant temperature ultrasonic stirring is continued for 12 hours; then the modified glass fiber cloth A is taken out and naturally dried.
[0058] (4) Impregnation with adhesive: The glass fiber cloth A obtained in step (3) is immersed in adhesive for 30 min at a temperature of 40° C.; then taken out and dried naturally to obtain glass fiber cloth B;
[0059] The preparation method of the glue solution is as follows:
[0060] 32.50g polycarbonate diol (Mn=2000) and 10g fluorinated polyol (Mn=1000, purchased from Wuhan Kemik Biopharmaceutical Technology Co., Ltd.) were dehydrated at 110-120°C with a vacuum degree of 0.09MPa for 1h, and then added to a reaction flask equipped with a thermometer, a stirring rod, and a reflux condenser. 11.7g solid MDI and 0.10g dibutyltin dilaurate were added under nitrogen protection, and the mixture was reacted at 80°C for 2h. After cooling to 55°C, butanone (the solid content was adjusted to 60%) was added, and 1.38g N-methyldiethanolamine) and 1g 11-(triethoxysilyl)-1-undecylamine and 0.5g (triethoxysilyl) methanol; when the temperature drops below 45°C, add 2.00ml acetic acid, react for 30min, adjust the pH to 5-6 with 5% dilute hydrochloric acid, cool to room temperature, add a mixture of ethanol and water (volume ratio of 1:3), and adjust the solid content to 30%.
[0061] (5) Molding: The glass fiber cloth B is dried at 180 degrees Celsius for 30 minutes and solidified to obtain a pressed pad.
[0062] Example 2
[0063] The difference between this embodiment and embodiment 1 is that the glass fiber cloth is not soaked in solution A and directly starts from step (2).
[0064] Example 3
[0065] The difference between this embodiment and embodiment 1 is that solution A is replaced with alkaline water: an aqueous solution saturated with sodium hydroxide.
[0066] Example 4
[0067] The difference between this embodiment and embodiment 1 is that step (2) and step (3) are not included.
[0068] Example 5
[0069] The difference between this embodiment and embodiment 1 is that the formulation of the glue solution in step (4) does not contain 10 g of fluorine-containing polyol, and an equal amount thereof is replaced by polycarbonate diol (Mn=2000).
[0070] Example 6
[0071] The difference between this embodiment and embodiment 1 is that the formula of the glue solution in step (4) does not contain 1 g of 11-(triethoxysilyl)-1-undecylamine and 0.5 g of (triethoxysilyl)methanol, but is replaced by N-methyldiethanolamine in equal amounts.
[0072] Performance Testing
[0073] 1. Buffering performance: Tested at 100℃, 90% RH, with a pressure of 150kg, and the area of the test sample is 1cm 2 , cushioning coefficient = (initial thickness of sample - thickness of sample during experiment) / initial thickness of sample × 100%.
[0074] 2. Buffering performance after aging: In an environment of 120℃, 90% rh, the area of the test sample is 1cm 2 After 200 times of pressing with a pressure of 200 kg, the cushioning performance was tested again. Cushioning coefficient = (initial thickness of sample - thickness of sample in experiment) / initial thickness of sample × 100%.
[0075] 3. Peel strength: The peel strength between the base fabric and the rubber material in the pressed cushion prepared in the example was tested according to GB / T 2792-2014 standard.
[0076] Table 1 Performance test results
[0077] Example Group Buffering performance, % Buffering performance after aging, % Peel strength N / mm Example 1 26.7 23.5 1.92 Example 2 22.1 13.4 1.18 Example 3 22.4 - 1.87 Example 4 18.8 - 1.35 Example 5 21.4 14.6 1.90 Example 6 22.0 15.9 1.25
[0078] The “-” in the above table means that after 200 times of lamination, the lamination pad was cracked, torn, or internally damaged.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A wet coating process for a fluorine-containing rubber press pad, characterized in that: The coating process is as follows: (1) Pretreatment of glass fiber cloth: immerse the glass fiber cloth in solution A for 30 min at a temperature of 40°C; (2) Preparation of deposition solution; (3) Impregnation and drying: impregnating the glass fiber cloth in the sedimentation liquid to obtain the modified glass fiber cloth A; (4) Impregnation with adhesive: The glass fiber cloth A obtained in step (3) is immersed in adhesive for 30 min at a temperature of 40° C.; then taken out and dried naturally to obtain glass fiber cloth B; (5) Molding: heating and curing the glass fiber cloth B and molding it; The composition of solution A in step (1) is: 95wt% water, 0.5wt% starch, 1wt% potassium chloride, 0.5wt% phosphate, 2wt% alkaloid, 0.5wt% potassium hydroxide, and 0.5wt% minerals; Steps (2) to (3) The components of the deposition solution include: ammonium chloride, water, ammonia water, and tetraethyl orthosilicate; The specific steps of step (2) and step (3) are as follows: S01 Dissolve 10.8g of ammonium chloride in 40.0g of ultrapure water, add 70.0mL of ammonia water, and dilute to 200mL with water; S02: 10 ml of the above solution, the glass fiber cloth obtained in step (1), and 826.7 ml of ultrapure water are mixed together, and 693.2 g of tetraethyl orthosilicate is slowly added dropwise at a constant temperature of 80° C. under ultrasonic stirring; after the addition is completed, the constant temperature ultrasonic stirring is continued for 12 hours; then, the modified glass fiber cloth A is taken out and dried naturally; Step (4) Immerse the glass fiber cloth A obtained in step (3) in the glue solution for 30 minutes at a temperature of 40° C. and then take it out and dry it naturally to obtain glass fiber cloth B; The preparation method of the glue solution is as follows: 32.50g of polycarbonate diol and 10g of fluorine-containing polyol are dehydrated at 110-120°C with a vacuum degree of 0.09MPa for 1h, and then added to a reaction flask equipped with a thermometer, a stirring rod, and a reflux condenser, 11.7g of solid MDI and 0.10g of dibutyltin dilaurate are added under nitrogen protection, reacted at 80°C for 2h, cooled to 55°C, butanone is added to adjust the solid content to 60%, 1.38g of N-methyldiethanolamine, 1g of 11-(triethoxysilyl)-1-undecylamine and 0.5g of (triethoxysilyl) methanol are added under condensation reflux; 2.00ml of acetic acid is added when the temperature drops below 45°C, the pH is adjusted to 5-6 with 5% dilute hydrochloric acid, and then cooled to room temperature, and a mixed solution of ethanol and water is added to adjust the solid content to 30%; wherein the volume ratio of ethanol to water is 1:3; Step (5) Dry the glass fiber cloth B at 180 degrees Celsius for 30 minutes to solidify and form a pressed pad.
Citation Information
Patent Citations
A post-treatment agent for electronic grade glass fiber cloth
CN105401423B
Wax-free impregnating agent for high-silica glass fibers and its preparation method
CN110937825B
Preparation method for modified PTFE copper-clad plate with high peeling strength
CN110948917A
Post-treatment enhancing method of TPU (Thermoplastic Polyurethane) workpiece
CN116023694A